Continuity and Change Among Canadian Mennonite Brethren. - Hamm, Peter M. (Wilfrid Laurier University Press, 1987)
More than 450 years after their birth in the Anabaptist movement, 125 years after their secession from Russian Mennonitism, and 60 years after their immigration to Canada, the Mennonite Brethren exhibit specific and measurable signs of sectarian viability and religious vitality. To explain the persistence of the sect, Hamm analyses the process of sacralization within the Canadian Mennonite Brethren Church - which ""safeguards identity, a system of meaning, or a definition of reality""--And the process of secularization - which ""erodes boundaries, dislodges stable structures, and destroys